Risk factors and perinatal outcome associated with low birth weight in a prospective cohort: is there a shift towards sustainable developmental goal 3 - Panda, Sandhyasri; Kishore M., Sai Sunil; M., Durga Devi; G., Mahalakshmi; S., Sirisha; Kiran, Maneesha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Low birth weight is a socio, economic, cultural and community based health issue which reflects responsibility and commitment of local and national administrative authorities. It continues to be a cause of short and long term adverse perinatal outcome with a bearing on adult non communicable health risks. Methods: This is a prospective observational and analytic study to know the prevalence, risk factors and perinatal outcome of LBW, from July 2017 to December 2018 in department of Obstetrics and Gynecology, MIMS Medical College, Andhra Pradesh, India. Maternal risk factors and outcomes associated with LBW were defined through risk ratios. Results: 721 infants including 116 LBW and 605 NBW born during study period were included in the study. Prevalence of LBW was 16%. Preterm birth accounted for 35%, FGR for 13.8% and SGA for 51.2% of them. Maternal factors like age <20 years and >35years, social status II to IV, below higher secondary education, house maker, primi gravida, grand multi para, BMI <18.5kg/M2 or >24.9kg/M2, Hb<11 gm% were having higher RR for LBW. LBW infants showed frequent association with oligo or polyhydramnious and hemorrhagic or turbid amniotic fluid. They had higher risks for non reassuring fetal heart rate changes, for induced delivery or an elective caesarean section. More often they needed NICU care for longer duration and showed a higher risk for malformations and neonatal mortality. Overall perinatal mortality was 5.54 per 1000 live birth. Conclusions: LBW is a risk factor for neonatal morbidity and mortality; which can be minimised by institutional delivery. High prevalence PTB (35%) warrants obstetricians to be more vigilant about indentifying the risk factors and adequate management planning. Constitutionally small baby at birth probably needs redefining normal birth weight for different ethnicity.